184k views
3 votes
For the following geometric sequence find the explicit formula. {12, -6, 3, ...}​

User Dathan
by
5.0k points

2 Answers

5 votes

Answer:


a_(n) = 12
(-(1)/(2)) ^(n-1)

Explanation:

The nth term of a geometric sequence is


a_(n) = a₁
(r)^(n-1)

where a₁ is the first term and r the common ratio

Here a₁ = 12 and r =
(a_(2) )/(a_(1) ) =
(-6)/(12) = -
(1)/(2) , then


a_(n) = 12
(-(1)/(2)) ^(n-1) ← explicit formula

User Bob Gilmore
by
4.2k points
3 votes

Answer:

It's geometric sequence where a_1=12, q=-\dfrac{1}{2}a

1

=12,q=−

2

1

So a_n=12\cdot\left(-\dfrac{1}{2}\right)^{n-1}a

n

=12⋅(−

2

1

)

n−1

User Prasanth S
by
5.0k points